Construction of Small‐Diameter Vascular Graft by Shape‐Memory and Self‐Rolling Bacterial Cellulose Membrane. Issue 11 (17th March 2017) - Li, Ying; Jiang, Kai; Feng, Jian; Liu, Jinzhe; Huang, Rong; Chen, Zhaojun; Yang, Junchuan; Dai, Zhaohe; Chen, Yong; Wang, Nuoxin; Zhang, Wenjin; Zheng, Wenfu; et al.
Abstract : Bacterial cellulose (BC) membranes with shape‐memory properties allow the rapid preparation of artificial small‐diameter blood vessels when combined with microfluidics‐based patterning with multiple types of cells. Lyophilization of a wet multilayered rolled BC tube endows it with memory to recover its tubular shape after unrolling. The unrolling of the BC tube yields a flat membrane, and subsequent patterning with endothelial cells, smooth muscle cells, and fibroblast cells is carried out by microfluidics. The cell‐laden BC membrane is then rerolled into a multilayered tube. The different cells constituting multiple layers on the tubular wall can imitate blood vessels in vitro. The BC tubes (2 mm) without cell modification, when implanted into the carotid artery of a rabbit, maintain thrombus‐free patency 21 d after implantation. This study provides a novel strategy for the rapid construction of multilayered small‐diameter BC tubes which may be further developed for potential applications as artificial blood vessels. Abstract : A method for the rapid preparation of artificial small‐diameter vascular structures from bacterial cellulose (BC) membranes with self‐rolling and tubular shape‐memory properties is described. By combining the shape‐memory BC membrane and microfluidics, multilayered cell‐laden tubular BC structures mimicking blood vessels can be produced for long‐term thrombosis‐free implantation in the rabbit carotid artery.